Extended Spectrum Beta-Lactamases (ESBLs)-producing Escherichia coli and Klebsiella pneumoniae among asymptomatic Out-patients in a University Health Centre - AM Deji-Agboola; OR Olaosebikan; E Adenipekun; OA Osinupebi; FA Olajubu (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2020)
Background: Asymptomatic carriage and spread of Extended-Spectrum Beta-Lactamase (ESBLs)-producing Enterobacteriaceae in the community are potential risk factors for transmission of infection. Objective: To determine the prevalence of ESBL resistant genes in Escherichia coli and Klebsiella pneumoniae isolated from asymptomatic out-patients. Methods: Using a questionnaire, demographic information, medical history, previous hospitalization and antibiotics used were obtained. Stool and urine samples were collected from 350 participants, cultured, and the susceptibility of the isolates to antibiotics and ESBL production were determined using the disk diffusion method. ESBL genes such as blaTEM, blaCTX, and blaSHV were identified using the Polymerase Chain Reaction. Results: Escherichia coli and Klebsiella pnuemoniae were identified from the stool samples (256; 69.9% and 89; 24.4% respectively) and urine samples (15; 4.1% and 6; 1.6% respectively). The isolates were susceptible to imipenem (330; 90.6%) and nitrofurantoin (307; 80.4%), most of the isolates were resistant to fluoroquinolones, cephalosporins, and aminoglycosides while all the isolates were resistant to ampicillin. The prevalence of ESBL was 29 (8.3%) and was observed in Escherichia coli (19; 7.0%) and Klebsiella pneumoniae (11; 12.0%), including a dual carriage. The ESBL carriers were resistant to the cephalosporins, fluoroquinolones and aminoglycosides. CTX-M (20; 66.7%), TEM (14; 46.7%), CTX-M and TEM genes co-existed in 9 (30.0%) while no SHV gene was detected in the isolates. Age, sex, prior hospitalization and antibiotics use did not predispose to ESBL carriage. Conclusion: Asymptomatic carriage of ESBL producing enterobacteria in the participants indicates that they can serve as a reservoir of the gene encoding for antibiotic resistance.